Translating James Joyce’s Dubliners: Confronting Literalness and Revision - O'Shea, José Roberto (ABEI Journal, 2009)
This short paper addresses the issues of literalness and revisión in literary translation. The case in point is my own translation of James Joyce’sDubliners into Brazilian Portuguese, published in Brazil in the early 1990s.